1994
DOI: 10.1029/94jc00527
|View full text |Cite
|
Sign up to set email alerts
|

The flux of overflow water through the Charlie‐Gibbs Fracture Zone

Abstract: We report the results of a set of measurements made within the Charlie-Gibbs Fracture Zone in 1988-1989. The principal dam sources are year-long current meter •rds, 16 in number, and 23 conductivity-temperature-depth stations. The aim was to determine the flux of overflow water passing westward out of the Iceland Basin in the eastern North Atlantic. Within the fracture zone, overflow water is defined either as having salinity greater than 34.94 at the present time or, more generally, as having a potential dens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
82
0

Year Published

1997
1997
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(85 citation statements)
references
References 17 publications
3
82
0
Order By: Relevance
“…For example, variability of roughly this period has been observed near the equator in satellite sea surface temperature [Legeckis, 1977], sea level [Wyrtki, 1978] It is more interesting to consider how this variability might be caused by the intrinsic dynamics of the northward abyssal flow. Resonances, similar to those occurring in musical wind instruments, arise in one-dimensional open channel flow [Lighthill, 1978] [Saunders, 1994;Schmitz and Hogg, 1978], the Denmark Strait [Dickson and Brown, 1994], the Verna Channel [Hogg et al, 1982], and a gap between the Ceara Rise and the MidAtlantic Ridge [Whitehead and Worthington, 1982]. We speculate that the periodicities of each will be dependent on the bathymetry upstream of the sill.…”
Section: Discussionmentioning
confidence: 99%
“…For example, variability of roughly this period has been observed near the equator in satellite sea surface temperature [Legeckis, 1977], sea level [Wyrtki, 1978] It is more interesting to consider how this variability might be caused by the intrinsic dynamics of the northward abyssal flow. Resonances, similar to those occurring in musical wind instruments, arise in one-dimensional open channel flow [Lighthill, 1978] [Saunders, 1994;Schmitz and Hogg, 1978], the Denmark Strait [Dickson and Brown, 1994], the Verna Channel [Hogg et al, 1982], and a gap between the Ceara Rise and the MidAtlantic Ridge [Whitehead and Worthington, 1982]. We speculate that the periodicities of each will be dependent on the bathymetry upstream of the sill.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier observations with moored current meter stations in the northern trench of the CGFZ yielded a mean westward transport of 2.5 Sv with, however, much larger variability than previously reported for the DSOW boundary current off Greenland [Dickson et al, 1990], including intermittent periods of eastward flow [Saunders, 1994]. Moored current observations at the eastern entry of the southern trench yielded no net throughflow [Dickson et al, 1980].…”
mentioning
confidence: 97%
“…A minor contribution also spills over the Wyville-Thomson Ridge. After flowing over the IFR and the FBC sills, and entraining ambient water, the resulting Iceland-Scotland overflow water (ISOW) has been observed to flow southwestward along the northwestern slope of the Iceland Basin [Saunders, 1996], and westward through the Charlie-Gibbs fracture zone (CGFZ) [Saunders, 1994]. It has been suggested that this flow through the CGFZ subsequently turns northward into the Irminger Sea, joining DSOW there [e.g., Dickson and Brown, 1994;Saunders, 2001].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, an isopycnic model, in the absence of entrainment parameterization, contains insufficient diapycnal mixing and consequently the overflow properties are retained over unrealistically long distances [Willebrand et al, 2001]. Transport estimates based on the long-term moored instrument arrays of Dickson and Brown [1994], Saunders [1994Saunders [ , 1996, Dickson et al [2008], and Bacon and Saunders [2010] have formed a valuable benchmark for evaluating model performance in simulating overflow transport, which has not been well documented in the past. Some, but not all, of these transport data were used in a recent numerical study by Chang et al [2009].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation